2019
DOI: 10.3389/fnins.2019.01058
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor ECoG Signal Features for BCI Control: A Comparison Between People With Locked-In Syndrome and Able-Bodied Controls

Abstract: The sensorimotor cortex is a frequently targeted brain area for the development of Brain-Computer Interfaces (BCIs) for communication in people with severe paralysis and communication problems (locked-in syndrome; LIS). It is widely acknowledged that this area displays an increase in high-frequency band (HFB) power and a decrease in the power of the low frequency band (LFB) during movement of, for example, the hand. Upon termination of hand movement, activity in the LFB band typically shows a short increase (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 89 publications
0
20
1
Order By: Relevance
“…Of these, 2 participants were implanted with a cBCI at the time of the interview. 9,24 The revised Amyotrophic Lateral Sclerosis Functional Rating Scale (ALSFRS-r 25 ) score was used to assess the level of paralysis and communication impairment of each participant. Responses to each item of the ALSFRS-r were described by the participant and caregiver and scored by both researchers independently.…”
Section: Participantsmentioning
confidence: 99%
“…Of these, 2 participants were implanted with a cBCI at the time of the interview. 9,24 The revised Amyotrophic Lateral Sclerosis Functional Rating Scale (ALSFRS-r 25 ) score was used to assess the level of paralysis and communication impairment of each participant. Responses to each item of the ALSFRS-r were described by the participant and caregiver and scored by both researchers independently.…”
Section: Participantsmentioning
confidence: 99%
“…Additionally, it may be challenging to establish long-term biocompatibility between the ECoG electrode grid and the brain. Although some recent ECoG BCI studies have shown promising results for ALS patients with relatively longer-term motor applications via a few (2 – 4) electrodes those were placed around the motor cortex [ 31 ]–[ 33 ], it is unknown how many electrodes are needed for speech production decoding. Moreover, prior ECoG studies have analyzed only part of the brain, as ECoG electrodes are typically implanted only into the areas prone to epileptic seizures.…”
Section: Introductionmentioning
confidence: 99%
“…In these patients, a robust HFB response was retained (Freudenburg et al 2019). Whether and/or how the LFB response was affected varied between studies.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies observed robust low frequency power decreases in patients with ALS and/or PLS (Bai et al 2010;Riva et al 2012;Proudfoot et al 2017). Other studies reported reduced power decreases in ALS (Kasahara et al 2012), or more variability between patients with ALS, tetraplegia and brainstem stroke, with only some patients showing robust low frequency power decreases (Höhne et al 2014;Freudenburg et al 2019). These studies suggest that whether low frequency power decreases are retained depends on the disease (progression) and the influence of closed-loop feedback training.…”
Section: Discussionmentioning
confidence: 99%